Strategy of Export Competitiveness Enhancement on Cashew Nut Commodity - Fauziyah, Elys; Aniyatussholihah, Aniyatussholihah; Hidayati, Dwi Ratna (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
Plantation is one of sub sector in agriculture with strategic role and contribution in the Indonesian economic. One of those commodities is cashew nuts. This research aimed to analyze competitiveness of cashew nuts in the international market, to identify factors affecting cashew nuts competitiveness, and to formulate strategy in enhancing cashew nuts competitiveness. The research method used was RCA, ISP, ECI and SWOT. Research result showed that RCA value showed that Indonesian cashew nuts is comparative disadvantage, but Indonesia is as exporter by seeing ISP value, and market share of Indonesian cashew nuts based on ECI value. However Indonesia tends to be exporter country and have good market share. Strategy of export competitiveness on cashew nuts can be applied by extending trade cooperation by joining and taking active role in the world trade organization, increasing cashew nuts productivity and socialization of information about international market of cashew nuts about international market of cashew nuts, exporting procedures, cashew nuts export, import policies, and other rules related to transaction of cashew nuts export-import to all stakeholders.